Implementation of Electronic Id Card Policy in The Protection of Cyber Crime at The Office of The Ministry of Home Affairs of The Republic of Indonesia Together with The Central Jakarta Metro Police - Dian Damayanti; Yusuf Ali; Ghazalie; Yulian Azhari (Communications of International Proceedings, 2021)
The development of the internet and cyber world has not brought positive progress. One of the negative things that often occurs in cyberspace is cybercrime. The loss of space and time boundaries on the Internet can affect anything. A cracker can get into the system without official permission. Some people who break into the system will tell you the weaknesses of the system but some of them use the weaknesses to gain advantage. Several strategies were created to ward off cybercrime. Cybercrime is not only carried out over the internet, but can be done via a network that can send signals such as telephone and email communications. Implementation of electronic id card policy in the protection of cybercrime at the office of the ministry of home affair of the republic of Indonesia together with the central Jakarta  Polda Metro Jaya implemented the law that applies to online crimes. Some of these rules have been implemented in the Criminal Code, including the Law on Electronic Information and Transactions (UUITE). With the implementation of this system, cybercrime cases will decrease every year. Implementation of electronic id card policy in the protection of cybercrime at the office of the ministry of home affair of the republic of Indonesia together with the central jakarta Polda Metro jaya. The results of this study are: to determine the implementation of regulations based on the adaptation of FRIT regulations to the implementation of cybercrime applications in Central Jakarta. These are facilities that can be enjoyed by the community and become the government's authority in legal matters. Then the implementation is enjoyed by people who commit cybercrime to solve the problem of extortion within the police, judiciary and prosecutors. This study used descriptive qualitative method. The conclusion of this study is to use the Edward III (1980) method. The implementation of this policy is influenced by four variables, namely: communication, resources, disposition, and bureaucratic structure. Implementation of the electronic ID card policy in cybercrime protection at the Ministry of Home Affairs office of the Republic of Indonesia together with Jakarta Pusat Polda Metro Jaya. successful because the implementation of the electronic ID card policy in cybercrime protection at the Ministry of Home Affairs office of the Republic of Indonesia together with Polda Metro Jaya Jakarta Pusat. so that the public and the implementers know what to do, where the goals and objectives of the policy must be transmitted to the target group, reduce distortions in implementation, reduce the number of crimes to achieve domestic security which includes maintaining security and society. order, order, and enforce the law, implement protection, protection and service to the community, and maintain public order by upholding human rights.
Keywords: Implementation of Policies; Electronic Id Cards; Cyber Crime; Protection; Impacts; and Information and Electronic Transactions Law.